Effect of genotype on callus induction and plant regeneration from leaf explants of sugarcane (Saccharum sp.) - GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD; ABRINI, Jamal; IDAOMAR, Mohamed; CHIBI, Fatiha; SKALI SENHAJI, Nadia (My University, 2005)
Nine sugarcane genotypes (CP59-73, CP63-588, CP80-314, SP71-1081, F160, L62-96, CP70-321, CP57- 614 and Clone III) were evaluated for their callus induction capacity, embryogenic callus production and plant regeneration ability. Leaf cylinders were used as explants using Murashige and Skoog (MS) based medium supplemented with 3 mg l-1 2,-4 dichlorophenoxyacetic acid. Plant regeneration was accomplished on hormone free modified MS medium supplemented with casein hydrolyzate. The genotypes tested showed high callus induction percentage (69 to 95%) and high embryogenic callus percentage (60 to 100%). These genotypes also showed excellent regeneration capacities, with regeneration percentages ranged between 88 and 100%. Significant differences were observed between genotypes for callus induction capacity, embryogenic response and plant regeneration ability indicating that these criteria are genotype dependent. Plant regeneration ability is highly correlated with embryogenic callus production. The in vitro regenerated plants were successfully rooted and well acclimatised in growth cabinet conditions.
Keywords: Tissue culture; embryogenic callus; genotypic variation; plant regeneration; sugarcane; leaf; explants.